The Effect Of Work Stress and Organizational Culture on Work Performance with Organizational Commitment as an Intervening Variable in BPJS Employment in Sumbagsel - Intriana Veronika Yulandri; Mesra B (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to examine the influence of work stress and organizational culture on work performance, with organizational commitment as an intervening variable, at BPJS Ketenagakerjaan in South Sumatra. This study used a quantitative approach with a survey method. The sample consisted of 70 employees, selected through a saturated sampling technique. Data were collected using a questionnaire and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results of the study indicate that organizational culture has a positive and significant influence on organizational commitment and job performance. Organizational commitment also has a positive and significant influence on job performance. Conversely, job stress has a negative and significant influence on organizational commitment and job performance. Furthermore, the indirect effect analysis shows that organizational commitment mediates the relationship between organizational culture and job stress on job performance. Therefore, strengthening organizational culture and managing job stress effectively are crucial to improving employee organizational commitment and job performance.